2013
DOI: 10.1007/978-3-642-40477-1_49
|View full text |Cite
|
Sign up to set email alerts
|

Helping Me Helping You: Designing to Influence Health Behaviour through Social Connections

Abstract: Abstract.Of key importance to avoiding significant health problems such as cardiac disease and stroke is eating nutritious foods and leading an active lifestyle. However, leading a healthy lifestyle remains elusive and obesity continues to increase in North America. We investigate how online social networks (OSN) can change health behaviour by blending theories from health behaviour and participation in OSNs. We designed, prototyped and evaluated an OSN, called VivoSpace, using factors derived from the blend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…(2006) conclude that “people are attracted to video games because they experience autonomy, competence, and relatedness while playing”(p. 2). In light of this, other studies use the flow theory (Kankanhalli et al., 2012; Korn, 2012), developed by Csikszentmihalyi (1990), and self-efficacy theory (Kamal et al., 2013; Sjoklint et al., 2013; Vassileva, 2012) by Bandura (1977) to predict learner behaviors and outcomes. In gamification, flow theory posits a certain level of challenge.…”
Section: Gamification Research: Conceptual Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2006) conclude that “people are attracted to video games because they experience autonomy, competence, and relatedness while playing”(p. 2). In light of this, other studies use the flow theory (Kankanhalli et al., 2012; Korn, 2012), developed by Csikszentmihalyi (1990), and self-efficacy theory (Kamal et al., 2013; Sjoklint et al., 2013; Vassileva, 2012) by Bandura (1977) to predict learner behaviors and outcomes. In gamification, flow theory posits a certain level of challenge.…”
Section: Gamification Research: Conceptual Approachesmentioning
confidence: 99%
“…On the other hand, the self-efficacy theory looks at the players’ perception of the games in terms of completion and winning (i.e., personal belief and ability to succeed necessitate their intentions to play). Other evident theories applied to gamification and education include the theory of planned behavior (Hamari & Koivisto, 2013; Vassileva, 2012), the theory of gamified learning (Ofosu-Ampong & Boateng, 2018), and uses and gratification theory (Kamal et al., 2013; Kankanhalli et al., 2012). Notwithstanding the various theories applied to gamification, the review identified a gap (disconnect) between theories and practice.…”
Section: Gamification Research: Conceptual Approachesmentioning
confidence: 99%
“…Some video game interventions designed for children with T1DM 9 , 25 - 26 and health in general 27 are described in the literature. Theories as The Elaboration Likelihood, Social Cognitive Theory (SCT), Self-Determination Theory (SDT), Behavioral Inoculation, and Transportation Theory are examples of health behavioral theories considered in studies that structured frameworks designed to prevent type 2 diabetes mellitus (T2DM) 23 , 15 and to influence changes in diet and physical activity 22 , 28 - 29 . The Theory of Planned Behavior guides a framework designed to increase adherence to treatment in T1DM patients 26 .…”
Section: Introductionmentioning
confidence: 99%
“…There are unclear presentations about how theoretical techniques might be applied to address studies' goals or how health behavior change determinants can be effectively included to promote behavior changes. 21,[26][27][28][29][30] The Social Cognitive Theory (SCT) 31 and Self-Determination Theory (SDT) 32 were selected to guide the theoretical framework of the video game. According to SCT, the behavior change is made from an individual sense of control regulated by forethought.…”
Section: Theorymentioning
confidence: 99%